A lab in the field: applications of real-time, in situ metagenomic sequencing. Issue 1 (20th August 2020) - Latorre-Pérez, Adriel; Pascual, Javier; Porcar, Manuel; Vilanova, Cristina
Abstract: High-throughput metagenomic sequencing is considered one of the main technologies fostering the development of microbial ecology. Widely used second-generation sequencers have enabled the analysis of extremely diverse microbial communities, the discovery of novel gene functions, and the comprehension of the metabolic interconnections established among microbial consortia. However, the high cost of the sequencers and the complexity of library preparation and sequencing protocols still hamper the application of metagenomic sequencing in a vast range of real-life applications. In this context, the emergence of portable, third-generation sequencers is becoming a popular alternative for the rapid analysis of microbial communities in particular scenarios, due to their low cost, simplicity of operation, and rapid yield of results. This review discusses the main applications of real-time, in situ metagenomic sequencing developed to date, highlighting the relevance of this technology in current challenges (such as the management of global pathogen outbreaks) and in the next future of industry and clinical diagnosis.